Investigating the potential of artificial intelligence for the employee from the perspective of AI-experts - Humpert, Lynn; Tihlarik, Amelie; Wäschle, Moritz; Anacker, Harald; Dumitrescu, Roman; Albers, Albert; Albert, Bruno; Röbenack, Silke; Pfeiffer, Sabine (2023 IEEE International Conference on Technology Management, Operations and Decisions, ICTMOD 2023, 2023)
Artificial intelligence (AI) has developed rapidly in recent months. In the form of chatbots, texting is becoming easier in our everyday lives. The potential for using this technology in industry is also growing. Small and medium-sized companies, in particular, are still underutilizing the opportunity to use AI in production and development as a competitive advantage or for sustainability goals. People are also often neglected in the introduction of new technologies. From a socio-technical perspective, employees must be explicitly considered as active cocreators and users of AI, whose knowledge of work processes and interactions with technology enriches the design of the humantechnology interface and, in the long run, the development of the technology itself. This paper examines how employees have used AI in the past, what their requirements are for their work and collaboration processes, and how they view the possibilities of technologies such as AI. Using a predominantly qualitative approach, this paper describes the socio-technical aspects that companies need to consider. The findings are consistent with previous literature and have been validated in expert workshops. This forms the basis for helping companies to develop this technology for themselves.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Engineering; Artificial Intelligence use cases; Human-Orientation; Stakeholder; User-centered design